Economical and safe support for underground excavations - Toledo Garay, Enrique (2011)
The most economical and safe support so far applied in Perú is implemented in Cobriza mine, called Shot-Fer. This method of application of rein forcer concrete tunnels and mine workings by Shotcrete or Gunite is a product of the research, based on the ACI 318-81 and the analysis of structures submitted arches Timoshenko books (Volume II, pp: 97-109) and Olivera Lopez (pp: 127-139); having calculated the workload under the proposal Stagg (pp: 103-124 and 193-222) and Hock (pp. 183-201). The Sho-Fer is quite different from NAM (new Austrian method) applied successfully in many countries. This method of application of reinforced concrete by Shotcrete, is much more efficient, lower cost and with greater versatility than the NAM to adapt to any changes in rocks mechanics that occur in mining operations, precisely in the insertion steel within the concrete mass